Analisis Kemampuan Keuangan Daerah Dalam Pelaksanaan Otonomi Daerah Di Kabupaten Merangin - Sartika, Novia (Jurnal Dinamika Manajemen, 2017)
This study aims to determine and analyze the development of regional own-source revenue (PAD), regional financial capability seen by the degree of fiscal decentralization, regional financial capacity seen by the ratio of self-sufficiency, as well as regional financial routine capabilities in Merangin district. The results of this study show that the development of regional original income in Merangin Regency during the 2007-2011 period showed fluctuating growth. The DDF for Merangin Regency is still on a very low interval scale because it is between 0-10%. As for the independence ratio, it is said to be very low, namely between 0-25%. And for routine ability it is said to be low because it is on a scale of 0-30%. The low routine capacity ratio is said to be low because Merangin Regency during the 2007-2011 period indicates that the regional government is still very dependent on the central government